IN-LINE SPUTTERING COATER OF HYDROPHOBIC ANTIREFLECTION COATING FOR SENSOR DISPLAYS - A. S. Myslivets; P. A. Rozel; E. A. Khakhlov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The aim of the work is to develop vacuum technological equipment for deposition an interference antireflection coating with the evaporation of a hydrophobic protective layer in a single vacuum cycle. To deposition an interference antireflection coating, the method of magnetron reactive sputtering in the alternating current mode with a frequency of 20 kHz is used. This method allows using of a wide range of sputtered materials and obtains stable and high-quality coatings on various substrates. To determine the optical characteristics, a spectrophotometer was used, which evaluated the transmittance and reflection in the visible region of the spectrum of electromagnetic radiation. To check the physical characteristics of the hydrophobic coating, abrasion test of the coating with metal wool with a load of 1 kg/cm2 was used. The novelty of the presented method is the combination of the liquid-phase coating method together with physical deposition in a vacuum without interrupting the process. This method allows increasing productivity and yield of suitable parts since the number of operations at the multi-stage stage of production of the touch display is reduced. After the development and adjustment of the Aurora G5 linear vacuum equipment, a stable and reproducible process for producing hydrophobic anti-reflective coatings over large areas with high performance was obtained. An antireflection coating was obtained with an average reflection coefficient of less than 0.6 % in the wavelength range of 400 to 700 nm. The adhesion test showed grade 0 according to the ISO classification. The resulting coatings have high hardness >9 H and abrasion resistance >5000 cycles. The result of this development and research is the introduction of vacuum processing equipment in the manufacturing process for the manufacture of anti-reflective hydrophobic coatings on touch displays.